Poetic Space of Intimacy and Movement: Re-Imagining the White Space of the Page in the Erasure Poetry of Carolyn Thompson, Sonja Johanson, and Lisa Huffaker - De Sanctis, Olivia (Pivot: A Journal of Interdisciplinary Studies and Thought, 2023)
This paper explores the transformation of poetic blank space in the work of three contemporary poets: Carolyn Thompson, Sonja Johanson, and Lisa Huffaker. Specifically, Thompson's Actions Speak Louder Than Words, and The Eaten Heart, Johnson's Untitled Erasure poem series, and Huffaker's 6 Images are compared and contrasted for their unique approaches to using the space of the page to add to the reading experience. The works discussed by each poet are erasure works that transform the page's white spaces surrounding the poem, using various additive or reductive methods to reimagine this space. If the white spaces surrounding a poem are often read as silences or voids, then using multi-modal techniques, these three poets transform these spaces in ways that signal intimacy and movement instead. This creation of intimacy and movement is explored through the intertextual jesters, an essential aspect of erasure poetry, along with the intersections between poetry and sculpture, bodily interactions with and implications within the texts, and poetry and avant-garde notions of cartography.